Standard equations for predicting the discharge coefficient of a modified high-performance side weir - Zaji, Amir Hossein; Bonakdari, Hossein; Shamshirband, Shahaboddin (Sharif University of Technology, 2017)
Side weirs are hydraulic structures that are used as discharge adjustments to divert the surplus water flowing from the main channel. Predicting the discharge coefficient is one of the most important parameters in the side weir design process. In practical situations, it is preferred to predict the discharge coefficient with simple equations. The goal of this study is to develop accurate standard equations for use in predicting the discharge coefficient of a high-performance, modified triangular side weir. The Particle Swarm Optimization (PSO) algorithm was used to optimize the parameters of the equations. Four different forms of the equations and two non-dimensional input combinations were used to develop the most appropriate model. The results obtained by our simple standard equations optimized by the PSO algorithm were compared with those of complex nonlinear regression equations, and our equations were more accurate in modeling the discharge coefficient. Our method reduced the error in the results by as much as 43% compared to the regression methods, and its simplicity makes it useful in solving practical problems.